Addressing the different paces of climate and air quality combustion emissions across the world - Fabio Monforti-Ferrario; Monica Crippa; Enrico Pisoni (iScience, 2024)
Summary: Greenhouse gases (GHG) and air pollutants (AP) share several anthropic sources but evolve differently in time across the various regions of the globe. Fossil and biological fuel combustion is by far the single process producing the highest amounts of both types of compounds. We have analyzed the paces of change of both GHG and AP emissions across the world and in some selected highly emitting regions using purposely designed indicators.We have observed that, overall, combustion processes are generally producing a lower amount of pollutants per unit of GHG emitted in 2018 than in 1970, with the noticeable exception of ammonia emissions in transport. Nevertheless, comparing countries at different development levels, evidence of possible further improvement clearly emerges, depending on the technological evolution of the most important emitting sectors and on the implementation of appropriate control measures and policies.